Correlation between Lipid Profile and D-dimer of Covid-19 Patients with Type 2 Diabetes Mellitus (TALENTA Publisher, Universitas Sumatera Utara, 2021)
Background. Lipids play a central role in viral infection, as they represent the structural foundations of cellular and viral membranes. The study aimed to examine the relationship between the D-dimer of T2DM patients with the lipid profile parameters of newly diagnosed COVID-19 patients. Method. This study uses secondary data, which is obtained from medical records of H. Adam Malik Medan Hospital between 2020-2021. The population of this study was all inpatients confirmed COVID-19 through RT-PCR SARS-CoV-2 swab examination. Results. There are 163 participants in this study. HbA1c values were high in T2DM patients with Covid-19, while lipid, and D-dimer profile values were still normal. Parameter of HbA1c, lipid and D-dimer profiles between men and women do not differ significantly. D-dimer is not correlated with HbA1c parameters and lipid profiles Conclusion. In this study, HbA1c values were high in T2DM patients with Covid-19, while D-dimer is not correlated with HbA1c parameters and lipid profiles